Melanoma and naevi with a globular pattern: confocal microscopy as an aid for diagnostic differentiation. (19th October 2015) - Benati, E.; Argenziano, G.; Kyrgidis, A.; Moscarella, E.; Ciardo, S.; Bassoli, S.; Farnetani, F.; Piana, S.; Cesinaro, A.M.; Lallas, A.; Borsari, S.; Pellacani, G.; et al.
Summary: Background: Dermoscopically, one of the most common findings in melanocytic lesions is a globular pattern. A regular globular pattern is a common finding in naevi. Melanoma can also show a globular pattern, with globules typically irregular in size, colour and distribution. Objectives: To investigate the likelihood of diagnosing melanoma according to distinct dermoscopic and confocal aspects. Methods: Dermoscopic and confocal aspects of 83 excised melanocytic lesions dermoscopically showing globules were analysed. Results: Our study population included 39 acquired melanocytic naevi, 16 Spitz naevi and 28 melanomas. Univariate analysis showed that regular distribution of globules on dermoscopy is associated with a ninefold lower risk for melanoma, whereas an irregular distribution is associated with an almost 10‐fold increased risk for melanoma. Concerning confocal features, dense nests are associated with a fivefold lower risk for melanoma, whereas loosely arranged nests are associated with an almost sixfold risk for melanoma; moreover, the presence of round cells is associated with a 17‐fold lower risk for melanoma, whereas pleomorphic cells are associated with an almost 16‐fold risk for melanoma. Conclusions: So that melanoma is not missed, clinicians should carefully analyse globular lesions in adults, focusing, in particular, on the distribution of globules and on the presence of confocal cytological atypia. Abstract : What's already known about this topic? The presence of specific dermoscopic and confocal findings in globular lesions is thought to be associated with the diagnosis of melanoma or naevi. However, a precise assessment of the specificity and sensitivity values of these variables has not been performed. What does this study add? When dealing with an adult patient with a globular lesion, the simultaneous presence of a regular globular pattern on dermoscopy and dense nests on reflectance confocal microscopy (RCM) should be considered a reassuring pattern suggestive of naevus. The presence of an irregular distribution of globules on dermoscopy (conveying about a 10‐fold increased risk for melanoma) and loosely arranged nests upon RCM should lead to prompt excision of a given globular lesion.